2020
DOI: 10.1177/1759720x20936060
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy computed-tomography-based discrimination between basic calcium phosphate and calcium pyrophosphate crystal deposition in vivo

Abstract: Background: Dual-energy computed tomography (DECT) is being considered as a non-invasive diagnostic and characterization tool in calcium crystal-associated arthropathies. Our objective was to assess the potential of DECT in distinguishing between basic calcium phosphate (BCP) and calcium pyrophosphate (CPP) crystal deposition in and around joints in vivo. Methods: A total of 13 patients with calcific periarthritis and 11 patients with crystal-proven CPPD were recruited prospectively to undergo DECT scans. Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…In addition, our study emphasizes the main potential clinical utility of DECT in calcium crystal–associated rheumatic and musculoskeletal diseases: characterizing larger (“macro”)/higher‐concentration crystal aggregates, rather than lowering the detection limit for early (“micro”)/lower‐concentration calcium crystal deposition not visible with conventional CT (7,10,11). This was supported by our phantom validation study, which showed that for all 5 DECT attenuation parameters, in particular DEI, CPP detectability improved with increasing synthetic CPP crystal concentration.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, our study emphasizes the main potential clinical utility of DECT in calcium crystal–associated rheumatic and musculoskeletal diseases: characterizing larger (“macro”)/higher‐concentration crystal aggregates, rather than lowering the detection limit for early (“micro”)/lower‐concentration calcium crystal deposition not visible with conventional CT (7,10,11). This was supported by our phantom validation study, which showed that for all 5 DECT attenuation parameters, in particular DEI, CPP detectability improved with increasing synthetic CPP crystal concentration.…”
Section: Discussionmentioning
confidence: 84%
“…The present study addressed one of the issues recently raised by the first clinical use of DECT in CPPD (7,(9)(10)(11): does early calcium crystal deposition alter DECT attenuation characteristics in menisci and articular cartilage prior to the appearance of detectable chondrocalcinosis by conventional CT? In this study, with a large enough sample size to detect clinically relevant changes in DECT attenuation characteristics, we found that with currently available DECT technology (7), the answer was no.…”
Section: Discussionmentioning
confidence: 99%
“…The use of DECT in the diagnosis of CPPD remains controversial. Although in vitro and in vivo studies show an encouragingly high capacity for differentiation between different calcium species [ 47 , 48 , 49 ], evidence of added diagnostic value of DECT vs. conventional CT remains sparse [ 50 , 51 ]. However, DECT may be a valuable tool for strengthening the understanding of the development of specific patterns of arthropathy in CPPD as it can be used to non-invasively detect tissue remodeling [ 52 ].…”
Section: Calcium Pyrophosphate Dihydrate Deposition (Cppd)mentioning
confidence: 99%
“…These specific concentrations were selected to replicate the X-ray attenuation characteristics of those crystals when imaged by conventional radiography, CT and dual-energy CT in vivo (figure 1). 6 The density of the agar-based lipogel background was intentionally increased to mimic the X-ray attenuation of hyaline cartilage (ie, 100–120 HU at 120 kVp). Each crystal suspension was removed from its Eppendorf tube and placed in a plastic container filled with US gel, next to the control (ie, crystal-free background) calibration phantom.…”
mentioning
confidence: 99%
“…(A) Conventional radiography, (B) CT and (C) ultrasound (US) of the various synthetic crystal suspensions with known increasing (from left to right in A, arrow; and from top to bottom in C) concentrations of calcium pyrophosphate (CPP) (26–109 mg/mL; red in B), hydroxyapatite (HA) (31–153 mg/mL; blue in B) and monosodium urate (MSU) (90–500 mg/mL, green in B). These specific concentration ranges were selected to replicate the X-ray attenuation characteristics of those crystals in vivo 6. the dashed line represents the crystal-free (0 mg/mL) agar-based lipogel background for reference.…”
mentioning
confidence: 99%